Urban public space development: themes and trends in the urban planning rhetoric - Ntakana, Khululekani; Mbanga, Sijekula; Mosiea, Tshepang (Frontiers in Built Environment, 2025)
A considerable body of research focusing on urban public space development has been published over the years in numerous academic journals internationally. This study reviews global research trends on this domain, driven by ongoing debates about whether these spaces fulfil their intended purposes. Its main goal is to map scholarly discourse on this topic in the 21st century, identifying key themes, emerging patterns, and changes over time. Understanding these trends is important for recognizing knowledge gaps, guiding future research, and informing urban planners and policymakers about challenges and opportunities in public space development. The study uses BiblioMagika and VOSviewer as bibliometric approaches to analyse 688 documents published from 1975 to 2024 sourced from the Scopus database. Advanced tools, including keyword co-occurrence, trend analysis, and multiple correspondence analysis, support a detailed exploration of the field. The findings reveal that there has been a significant upward trajectory in research output, beginning with a single publication in 1975 and culminating in 2023 with 76 publications. Kang Jian from the University College London in the United Kingdom is revealed to be the leading scholar and Ghent University in Belgium emerges as leading institution in this domain. Although limited to a single database, the research offers a comprehensive temporal and thematic overview of academic work on urban public spaces. Its findings are valuable for scholars, practitioners, and decision-makers seeking to align future research and urban planning strategies with current developments in the field.